2022
DOI: 10.1172/jci157975
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β–dependent extravasation of preexisting lung-restricted autoantibodies during lung transplantation activates complement and mediates primary graft dysfunction

Abstract: Preexisting lung-restricted autoantibodies (LRAs) are associated with a higher incidence of primary graft dysfunction (PGD), although it remains unclear whether LRAs can drive its pathogenesis. In syngeneic murine left lung transplant recipients, preexisting LRAs worsened graft dysfunction, which was evident by impaired gas exchange, increased pulmonary edema, and activation of damage-associated pathways in lung epithelial cells. LRA-mediated injury was distinct from ischemia-reperfusion injury since deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, the presence of alloantigens may predispose to C4d deposition in grafts (8). While we showed that these early graft-infiltrating B cells are not instrumental in secreting LRAs (43), whether they produce alloantibodies responsible for complement deposition and antibody-mediated rejection is unclear and warrants further investigation.…”
Section: Human Samplesmentioning
confidence: 69%
“…However, the presence of alloantigens may predispose to C4d deposition in grafts (8). While we showed that these early graft-infiltrating B cells are not instrumental in secreting LRAs (43), whether they produce alloantibodies responsible for complement deposition and antibody-mediated rejection is unclear and warrants further investigation.…”
Section: Human Samplesmentioning
confidence: 69%
“…Although antibody-mediated lung damage is a major contributing factor in transfusion-related acute lung injury (TRALI) ( 9 ), autoimmune lung disease (for example, coatomer subunit α [COPA] syndrome) ( 10 ), as well as primary graft dysfunction (PGD) occurring after lung transplantation ( 11 ), the mechanism by which antigen-antibody complexes activate the complement system to induce lung damage remains unclear. A theory that has increasingly gained traction involves the formation of IgG hexamers from IgG1 and IgG3 antibodies on antigenic surfaces by Fc-domain interactions that result in complement activation and increased deposition on these target surfaces ( 2 , 12 ).…”
Section: Antibody-mediated Lung Damagementioning
confidence: 99%
“…In addition, the Bacteroides uniformis was negatively associated with IL-1β and IL-12, which indicated that the gut microbiome is involved in allograft diseases possibly via modulating host immune responses in lung transplant. 24,25 Alternation of fecal metagenome correlates with serum metabolites Next, we asked which environmental factors explain the levels of the altered gut microbiome. Serum metabolites are known to play a key role in mediating the metabolic and immune interactions between the microbiome and its host, thus providing a fundamental view into the complex dynamics of environmental exposures.…”
Section: Alternation Of the Fecal Microbiome In Pulmonary Disordersmentioning
confidence: 99%